Overcoming the blood–brain barrier in neurodegenerative disorders and brain tumours. Issue 6 (13th July 2020) - Ebrahimi, Zahra; Talaei, Sam; Aghamiri, Shahin; Goradel, Nasser Hashemi; Jafarpour, Ali; Negahdari, Babak
Abstract : Drug delivery is one of the major challenges in the treatment of central nervous system disorders. The brain needs to be protected from harmful agents, which are done by the capillary network, the so‐called blood–brain barrier (BBB). This protective guard also prevents the delivery of therapeutic agents to the brain and limits the effectiveness of treatment. For this reason, various strategies have been explored by scientists for overcoming the BBB from disruption of the BBB to targeted delivery of nanoparticles (NPs) and cells and immunotherapy. In this review, different promising brain drug delivery strategies including disruption of tight junctions in the BBB, enhanced transcellular transport by peptide‐based delivery, local delivery strategies, NP delivery, and cell‐based delivery have been fully discussed.